ASOSIASI POHON DENGAN EPIFIT Hoya spp. DI TAMAN NASIONAL BUKIT DUABELAS Tree Association with Epiphytes Hoya spp. in Bukit Duabelas National Park - Inggar Damayanti; Iskandar Z. Siregar; Sri Rahayu (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2017)
In the tropical rainforests of Jambi, Sumatera, a particular group of epiphytes, species in the genus Hoya, have significant potential to be developed as commercially valuable ornamental plants, because of the uniqueness and beauty of their flowers. Hoya spp. are epiphytic vines whose survival depends largely on the presence of carrier trees, i.e. phorophyte trees. The study reported here was conducted to identify the level of epiphytic association between phorophyte trees and identified Hoya species. The study found four Hoya species, namely: Hoya rintzii, Hoya revoluta, Hoya coronaria, and Hoya cf. caudata. The four species of Hoya were found growing on eleven different species of phorophyte trees. Based on the results of t-contingency tables it was found that there is no association between particular Hoya species and the particular phorophyte tree species. This conclusion was supported by the calculation of Jaccard association indices demonstrating that the association between Hoya spp. and phorophyte tree species is relatively weak. Crown cover and the diameter of the tree are two habitat variables that affect the presence of Hoya revoluta at the sites. The presence of Hoya caudata was influenced by the variable temperature, while the presence of Hoya coronaria was associated with humidity, but the degree of association was relatively weak. The most significant variables affecting the presence of Hoya rintzii were tree height and elevation.Key word: association, ephyphites, Hoya spp, phorophyte.